2008
DOI: 10.1111/j.1747-4477.2007.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependence of coronal seal of temporary materials used in endodontics

Abstract: The aim of this in vitro study was to compare parametrically the coronal seal ability over different periods of times of four restorative materials used to seal the pulpal access cavity after endodontic treatment. One hundred and thirty-five mandibular premolars were divided randomly into three time groups (1, 2 and 4 weeks), each of which was in turn divided into four subgroups. Each subgroup was restored using one of four restorative materials: Coltosol, glass ionomer cement (GIC), zinc phosphate (ZP) cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 27 publications
3
26
0
7
Order By: Relevance
“…In relation to the temporary filling coronary studies have shown that Coltosol was significantly better in preventing microleakage other temporary materials (2,9). However, the hygroscopic expansion of Coltosol in a cavity may lead to cusp deflection, infraction development and fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the temporary filling coronary studies have shown that Coltosol was significantly better in preventing microleakage other temporary materials (2,9). However, the hygroscopic expansion of Coltosol in a cavity may lead to cusp deflection, infraction development and fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Use of glass ionomer cements as temporary restoration materials during endodontic treatment has been investigated in a number of studies with various results. 2,6 In this study, however, Fuji II showed marginal leakage as high as that observed in the positive controls. This has been attributed to its sensitivity to manipulation and polymerization shrinkage resulting in a potential avenue of microleakage.…”
Section: (A) (B) (C) (D)mentioning
confidence: 52%
“…2 Many temporary restorative materials have been studied to determine their ability to seal endodontic access preparations. [2][3][4][5][6] Most studies have examined the materials in simple access preparations within an intact tooth structure. In clinical practice, however, the use of these materials frequently involves the restoration of a multisurface cavity preparation necessitated by the removal of caries or defective restorations.…”
Section: Introductionmentioning
confidence: 99%
“…6 There is still lack of evidence in the literature regarding the effect of saliva on temporary restorations. 7 Hence, we evaluated the effect of saliva on the coronal leakage of temporary restorations.…”
Section: Introductionmentioning
confidence: 99%